Flexibility Control of Two‐Dimensional Coordination Polymers by Crystal Morphology: Water Adsorption and Thermal Expansion. Issue 72 (24th November 2021) - Ohtani, Ryo; Yoshino, Haruka; Yanagisawa, Junichi; Ohtsu, Hiroyoshi; Hashizume, Daisuke; Hijikata, Yuh; Pirillo, Jenny; Sadakiyo, Masaaki; Kato, Kenichi; Shudo, Yuta; Hayami, Shinya; Le Ouay, Benjamin; et al.
Abstract: Layer flexibility in two‐dimensional coordination polymers (2D‐CPs) contributes to several functional materials as it results in anisotropic structural response to external stimuli. Chemical modification is a common technique for modifying layer structures. This study demonstrates that crystal morphology of a cyanide‐bridged 2D‐CP of type [Mn(salen)]2 [ReN(CN)4 ] (1 ) consisting of flexible undulating layers significantly impacts the layer configuration and assembly. Nanoplates of 1 showed an in‐plane contraction of layers with a longer interlayer distance compared to the micrometer‐sized rod‐type particles. These effects by crystal morphology on the structure of the 2D‐CP impacted the structural flexibility, resulting in dual‐functional changes: the enhancement of the sensitivity of structural transformation to water adsorption and modification of anisotropic thermal expansion of 1 . Moreover, the nanoplates incorporated new adsorption sites within the layers, resulting in the uptake of an additional water molecule compared to the micrometer‐sized rods. Abstract : Preparing nanoplates of flexible two‐dimensional coordination polymers provides significant structural changes involving the contraction of undulating layers. Such crystal morphology and size effects on layer structures modulate the dual functions of water adsorption and anisotropic thermal expansion.